The ascending branch of the lateral circumflex femoral artery penetrating the posterior division of the femoral nerve - Kim, Hankyu (Anat Cell Biol, 2021)
Understanding anatomic variations in neurovascular structure inside the femoral triangle is crucial for regional anesthesiologists performing femoral nerve block. During routine dissection of a cadaver, an ascending branch of the lateral circumflex femoral artery with an anomalous course passing through the femoral nerve, specifically the posterior division, was identified inside the femoral triangle on the left thigh. The novel variation identified in this study occurred in an early stage of prenatal development. Recognition of this anatomic variation will be helpful for reducing unexpected complications during the femoral nerve block and the tensor fascia latae flap. Penetration of the posterior division of the femoral nerve by the arterial branch might cause pain or paresthesia of the medial aspect of the leg in the distribution of the saphenous nerve.